Assessment in occupational therapy and physical therapy - Van Deusen, Julia, ....-; Brunt, Denis, ....- (Philadelphia : Saunders, 1997)
Contents: -------- 1. Overview of measurement theory 2. Component assessments of the adult 3. Assessment of central nervous system function of the adult 4. age-related assessment 5. assessment of activities of daily living
Keywords: ADL; Ergotherapie